2023
DOI: 10.1111/jne.13254
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and prolonged food restriction differentially affect GH secretion independently of GH receptor signaling in AgRP neurons

Abstract: Growth hormone (GH) receptor (GHR) is abundantly expressed in neurons that co‐release the agouti‐related protein (AgRP) and neuropeptide Y (NPY) in the arcuate nucleus of the hypothalamus (ARH). Since ARHAgRP/NPY neurons regulate several hypothalamic–pituitary‐endocrine axes, this neuronal population possibly modulates GH secretion via a negative feedback loop, particularly during food restriction, when ARHAgRP/NPY neurons are highly active. The present study aims to determine the importance of GHR signaling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…We have observed a trend for glucagon to increase in PI3Ka AdQ mice at 90 minutes, but this trend was quantitatively marginal and statistically not significant (Figure 4F). Growth hormone was undetectable in plasma during the experiments (Figure 4G), which is consistent with a recent study showing that growth hormone levels are drastically reduced in mice fasted overnight (de Sousa et al, 2023).…”
Section: Adipocyte Pi3k Links Adipostasis With Insulin Secretionsupporting
confidence: 92%
“…We have observed a trend for glucagon to increase in PI3Ka AdQ mice at 90 minutes, but this trend was quantitatively marginal and statistically not significant (Figure 4F). Growth hormone was undetectable in plasma during the experiments (Figure 4G), which is consistent with a recent study showing that growth hormone levels are drastically reduced in mice fasted overnight (de Sousa et al, 2023).…”
Section: Adipocyte Pi3k Links Adipostasis With Insulin Secretionsupporting
confidence: 92%
“…In addition, it has been suggested that the state of GH resistance is an adaptive response to reduced energy intake due to poor nutrition [ 27 ]. Previously, nutritional status has been shown to dictate the effects of GH [ 32 ], with normal or elevated GH levels during prolonged nutrient deprivation and concomitant decreases in serum IGF-1 levels [ 32 , 33 , 34 ]. The observed reduction of IGF-1 level in serum is affected by a decreased Igf1r mRNA level in the liver, where most circulating IGF-1 is produced [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential for GH modulation of the activity of neurons co‐releasing agouti‐related peptide (AgRP) and neuropeptide Y (NPY) and how this may, in turn, affect the pattern of GH secretion is explored in the article by de Sousa et al 3 Using animals fasted for different durations, this study shows that the impact on the pattern and level of GH secretion is dependent on the length of time animals have food restricted, which may explain conflicting effects described in the literature. The authors highlight the importance of measuring pulsatile GH secretion at multiple time points to determine the effect of fasting but also show that this pattern of secretion is independent of GH signalling to AgRP/NPY neurons.…”
mentioning
confidence: 99%